The Implementation of Character Management Through Habit At SDIT Nurul Huda Purbalingga - Dirsan, Dirsan (Prosiding University Research Colloquium, 2021)
The cause of low character is the education system that emphasizes intellectual development rather than character development. Efforts in character education for students are by inculcating character through habituation. This study aims to describe and critically analyze the Cultivation of Character Through Habituation at SDIT Nurul Huda Purbalingga. This type of research is field research or field research where researchers go directly to the field to obtain data and information related to the research conducted. The activities carried out were time discipline, practicing 3S and kissing the teacher's hand when the child shook hands with the teacher, morning tahsinul qiro'ah, dhuha prayer, praying in congregation, asking permission, eating according to etiquette, not eating snacks outside school, and other. The implementation of character planting through habituation is carried out through 3 stages, namely the stage of knowledge (knowing), implementation (acting), and habituation (habit). The creation of a conducive atmosphere and adequate facilities also support the process of implementing character through routine habituation.